MAIN CHARACTERISTICS IN THE NOVEL PULANG BY TERE LIYE - Lovelista, Hadelberta Uyi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study describes the character and character development of the main character in the novel Pulang based on the behaviorist psychology approach of BF Skinner. This research uses a descriptive method with a qualitative research form. The data source in this study in the novel Pulang by Tere Liye, with data consisting of quotations in the form of sentences, paragraphs, or dialogues found in the novel. The results of this study indicate that: 1) the main character in the novel Pulang by tere Liye has 6 characteristics, namely smart, tough, caring, doesn't like to beat around the bush, and leadership. 2) The character development of the main character in the novel Pulang by Tere Liye consists of two forms of development, which are positive and negative, namely stubbornness turning into open-mindedness and toughness turning into starting to feel rear. 3) Module of Indonesian language learning for 12th grade students in odd materials in schools related to characters, and can be used as a reference for further research.